Polycaprolactone-Based, Porous CaCO3 and Ag Nanoparticle Modified Scaffolds as a SERS Platform With Molecule-Specific Adsorption - Saveleva, Mariia; Prikhozhdenko, Ekaterina; Gorin, Dmitry; Skirtach, Andre G.; Yashchenok, Alexey; Parakhonskiy, Bogdan (Frontiers in Chemistry, 2020)
Surface-enhanced Raman scattering (SERS) is a high-performance technique allowing detection of extremely low concentrations of analytes. For such applications, fibrous polymeric matrices decorated with plasmonic metal nanostructures might be used as an operative, flexible SERS substrates foranalysis of analytes in many application. In this study, a three-dimensional SERS substrate consisted of CaCO3-mineralized electrospun (ES) polycaprolactone (PCL) fibrous matrix decorated with silver (Ag) nanoparticles is developed. Such modification of the fibrous substrate allowed a significant increase of SERS signal amplification to be achieved. Functionalization of fibres by porous CaCO3 (vaterite) and Ag nanoparticles provides an effective approach of selective adsorption of biomolecules and their precise detection by SERS. This new-developed SERS substrate represents a promising biosensor platform with selectivity to low and high molecular weight molecules; potential applications of such biosensors are discussed.